Comparative Study of Lateral Anal Sphincterotomy Versus Botulinum Toxin Injection for Treatment of Chronic Anal Fissure - Aslam, Asim; Malik, Muhammad Jalil; Sundas, Madhia; Khawaja, Farukh Gulzar; Nasir, Ammad ud din; Abbas, Shahid (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare lateral internal sphincterotomy with injection Botulinum toxin for chronic anal fissure treatment in terms of improvement in mean postoperative pain, frequency of healing and fecal incontinence.Study Design: Quasi-experimental study.     Place and Duration of Study: Combined Military Hospital, Rawalpindi, Pakistan, from Feb to Aug 2019.Methodology: Among the patients reporting to Surgical Unit II of Combined Military Hospital Rawalpindi, Pakistan. 80 individuals with chronic anal fissure, 12- 60 years of age were included in the study. Patients who have recurrent disease, fistula in ano, hemorrhoids, cardiovascular disease, and coagulopathies were excluded. Group-A patients had lateral anal sphincterotomy as an elective case under spinal anesthesia. Whereas Botulinum Toxin A was administered under local anesthesia in internal anal sphincter in Group-B patients in the outpatient department (OPD). Patients were followed up at 1, 4, 8, and 12 weeks in the OPD.Results: In Group-A, mean postoperative pain was found to be 3(4–2) in Group-A, and in Group-B was found to be 2( 2–1)  with a significant p-value